Forty-Five Years of LIS Research Evolution, 1971–2015: An Informetrics Study of the Author-Supplied Keywords - Onyancha, Omwoyo Bosire (Publishing research quarterly, 2018)
This article sought to investigate the evolution of library and information science by tracking the author-supplied keywords in the research articles published in the domain between 1971 and 2015. Data was extracted from Thomson Reuters’ citation mainstream indexes and analysed using the VosViewer computer-aided software to obtain author-supplied keyword frequencies in each decade since 1971. We identified the most salient and common research themes in LIS and how the themes have evolved, by delving into the author-supplied keywords to proxy research themes in the field domain. Results indicate that the field of LIS has evolved in terms of its subject focus from information systems design and management in the 1970s to scientific communication, information storage and retrieval, information access, information and knowledge management, and user education in 2015. The application of ICTs in LIS practice and education, too, has emerged as a prominent topic in the field. These issues have the potential of shaping or have shaped the LIS curriculum in some LIS schools in the continent.